Pengembangan Instrumen RDQA Untuk Surveilans Epidemiologi DBD Di Dinas Kesehatan Kota Tarakan - Haikal Haikal; Martini Martini; Eko Sediyono (Jurnal Manajemen Kesehatan Indonesia, 2019)
In 2016 from 7 Puskesmas in Tarakan City, 4 (four) Puskesmas (58%) sent their reports above the 5th of each month. There is still a mismatch of the number of source data with the results of recapitulation such as the number of DHF cases in Tarakan DHO with the number of DHF cases in the Ministry of Health Republic of Indonesia SKDR as well as the incompatibility of the reporting format by recording surveillance staff. The purpose of this study was to develop a Routine Data Quality Assessment (RDQA) instrument for DHF Epidemiological Surveillance in Tarakan City Health Office. The type of research used is Research and Development. The total subjects of the study were 9 people with details of 7 data management officers in the Puskesmas in the Tarakan DKK working area and 1 person in charge of the DHF Program in Tarakan DKK. The steps in this study, namely: (1) Potential and problems, (2) Data Collection (3) Product Design (4) Design Validation (5) Design Revision (6) Product Trial (7) Product Revision (8) Trial Use. The results of this study are that data quality assessment instruments have been developed according to RDQA and routine data quality assessments by the Ministry of Health with R & D research methods modified with eight indicators namely timeliness, data availability, data completeness, monitoring and evaluation unit capabilities, reporting indicators and guidelines, data collection and reporting format, data management process, linkages with the national reporting system and the use of data for decision making. The results of the assessment of the instruments developed, namely the aspect of content feasibility has an average value of 81%, the feasibility aspect of presentation is 78% and language assessment aspects 81%. Based on the results of the assessment of the three aspects assessed in the development of the RDQA instrument, a good conclusion is reached, but there are general recommendations given both by the Chair of the DHF Program in the DHO and the Epidemiological Surveillance Data Management Officer in DHO and Puskesmas, namely the use of modules and manuals RDQA instrument.